2009
DOI: 10.2737/fpl-rp-659
|View full text |Cite
|
Sign up to set email alerts
|

Profile 2009: softwood sawmills in the United States and Canada

Abstract: The use of trade or firm names in this publication is for reader information and does not imply endorsement by the United States Department of Agriculture (USDA) of any product or service.The USDA prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or a part of an individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Timber production in California had stabilized in the early part of the last decade but has experienced a significant decline in the last few years ( (Spelter et al, 2009). In California, the loss in capacity during this time was 25 percent.…”
Section: Condition Of the Forest Products Sectormentioning
confidence: 99%
“…Timber production in California had stabilized in the early part of the last decade but has experienced a significant decline in the last few years ( (Spelter et al, 2009). In California, the loss in capacity during this time was 25 percent.…”
Section: Condition Of the Forest Products Sectormentioning
confidence: 99%
“…The boreal forest zone of northeastern North America is a major source of softwood lumber for both domestic and export markets [1]. However, wood processing industries in the region have been severely affected by the recent global economic downturn and the resulting fall in demand for structural wood products [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, wood processing industries in the region have been severely affected by the recent global economic downturn and the resulting fall in demand for structural wood products [1,2]. In remote areas (e.g., northern Quebec, Canada), the situation has been exacerbated by high harvesting and transport costs, which have increased the pressure to add value to the existing resource [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Capacity for 2012 was developed from the FIDACS census of California's forest products industry. Capacity for previous years was estimated from previous industry censuses (Howard and Ward 1991, Morgan et al 2004, Ward 1995 and for intervening years based on reported mill closures, openings, and expansions (Ehinger 2012, Random Lengths 1976-2013, Spelter et al 2009). …”
Section: Input and Output Capacitymentioning
confidence: 99%